Persepsi Guru Terhadap Pembelajaran Tatap Muka Pasca Pembelajaran Daring Dimasa Pandemi - Alim Siregar; Wirdanengsih Wirdanengsih; Relly Anjar Vinata Wisnu Saputra (Universitas Negeri Padang, 2022)
This study aims to determine the teacher's perception of face-to-face learning after online learning during the pandemic at SMA N 3 Padang. It is interesting to study the teacher's perception of the change in learning from online learning to face-to-face learning. This research is analyzed with Alferd Schutz's phenomenological theory which explains how to interpret or understand social action through interpretation, where the interpretation clarifies the true meaning. The perspective used by Schutz in understanding other people's awareness and self-awareness is the concept of intersubjectivity, namely the life of the world or daily life, in this theory there are two aspects to consider, namely knowledge and action. The method used in this research is to use a qualitative approach with the type of study intrinsic case. The technique of taking informants was carried out by random sampling, namely by taking random samples, with a total of 19 informants, namely teachers at SMA N 3 Padang who were more deeply involved in teachers who teach in the social studies section. Data collection techniques were carried out by means of non-participant observation, in-depth interviews and documentation studies. To obtain data validity, data triangulation was carried out. The data analysis technique used the Milles and Huberman model. The results of this study indicate the teacher's perception of face-to-face learning after online learning during the pandemic is based on the phenomenology that occurs, namely the change in online learning into full face-to-face learning.